2007
DOI: 10.1111/j.1741-3737.2007.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Cohabitation in the Philippines: Attitudes and Behaviors Among Young Women and Men

Abstract: We examine data from a national survey of 15 -27 year olds in the Philippines to assess attitudes toward marriage and cohabitation, and we analyze the marital and nonmarital union experiences of 25 -27 year olds. We find that attitudes toward cohabitation remain quite conservative among young Filipinos, although men view cohabitation more favorably than do women. We also find that men's socioeconomic status affects their ability to enter unions, particularly marriage, whereas women's union formation patterns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Similar to another study from the Philippines by Williams, et al, religiosity and educational attainment appeared to influence women’s life event patterns, yet this was not the case for young men(Williams et al 2007). This is in contrast to other findings from Cebu, however, indicating no influence of religiosity for either young men or women and increased risk of sexual debut among young men with higher education (Hindin 2006).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to another study from the Philippines by Williams, et al, religiosity and educational attainment appeared to influence women’s life event patterns, yet this was not the case for young men(Williams et al 2007). This is in contrast to other findings from Cebu, however, indicating no influence of religiosity for either young men or women and increased risk of sexual debut among young men with higher education (Hindin 2006).…”
Section: Discussionsupporting
confidence: 74%
“…In the two previous studies from Cebu, similar effects of urban residence were found for young males (Upadhyay and Hindin 2006; 2007). These findings point to the roles that societal expectations and gender norms may have on the upbringing and socialization of young girls and boys (Williams et al 2007), as well as the role of context and situational factors that may make some adolescents more likely to adopt these non-traditional (and perhaps higher risk) patterns. Data from the developing world is quite limited in this arena; however, evidence suggests that the prevalence of risk behaviors such as tobacco use, alcohol and substance abuse, is increasing due to the pressures of increased urbanization, poverty, and reduced social support (Uchtenhagen 2004).…”
Section: Discussionmentioning
confidence: 85%
“…Although families traditionally played a primary role in arranging courtship and marriage in the Philippines, courting in recent decades has gradually moved toward males and females meeting independent of familial control (35). Men's romantic prospects may thus be increasingly contingent on malemale competition, particularly in social and economic domains (36). This trend has likely increased the potential for high T to factor into male mating success.…”
Section: Discussionmentioning
confidence: 99%
“…Cohabitation is considered one of the signature elements of the SDT (Lesthaeghe and Neidert 2006; McLanahan 2004; Sobotka, Zeman, and Kantorová 2003; Surkyn and Lesthaeghe 2004). While the prevalence of cohabiting unions varies by region, numerous studies have shown growing cohabitation rates during recent decades in both Western societies and some Asian societies (Dominguez-Folgueras and Castro-Martin 2013; Heuveline and Timberlake 2004; Raymo, Iwasawa, and Bumpuss 2009; Williams, Kabamalan, and Ogena 2007). The number of cohabitating couples in the United States, for example, increased from about 500,000 in 1970 to about 7 million in 2010 (US Census Bureau 2011), and the proportion of women aged 19–44 who ever cohabited increased from 33 percent in 1987 to 60 percent in 2010 (Manning 2013).…”
Section: Cohabitation As a Form Of Unionmentioning
confidence: 99%